Functional characterization of the tomato HAIRPLUS gene reveals the implication of the epigenome in the control of glandular trichome formation. Issue 1 (28th January 2022) - Fonseca, Rocío; Capel, Carmen; Yuste-Lisbona, Fernando J; Quispe, Jorge L; Gómez-Martín, Cristina; Lebrón, Ricardo; Hackenberg, Michael; Oliver, José L; Angosto, Trinidad; Lozano, Rafael; Capel, Juan
Abstract: Trichomes are specialised epidermal cells developed in the aerial surface of almost every terrestrial plant. These structures form physical barriers, which combined with their capability of synthesis of complex molecules, prevent plagues from spreading and confer trichomes a key role in the defence against herbivores. In this work, the tomato gene HAIRPLUS ( HAP ) that controls glandular trichome density in tomato plants was characterised. HAP belongs to a group of proteins involved in histone tail modifications although some also bind methylated DNA. HAP loss of function promotes epigenomic modifications in the tomato genome reflected in numerous differentially methylated cytosines and causes transcriptomic changes in hap mutant plants. Taken together, these findings demonstrate that HAP links epigenome remodelling with multicellular glandular trichome development and reveal that HAP is a valuable genomic tool for pest resistance in tomato breeding.